Effects of Superstitious beliefs, Old Customs and Practices on Human Health - Ramaswamy, R.S.; Madhumithaa, S.R.; Kavitha, G. (Unit of Siddha Medicine, University of Jaffna, Kaithady, Sri Lanka, 2020)
Siddha medicine ensures physical, mental and social well- being.Many superstitious beliefs, old customs and ancient practices had positive effects on human health. In Siddha and Tamil literature we can find views/descriptions about many such beliefs, customs and practices and their health benefits. This paper aims to establish the scientific reasons behind such beliefs, customs and practices and to create awareness in this regard. To establish that the superstitious beliefs, old customs and practices followed in olden days have significant beneficial effects on human health. To create awareness among the public about such vanishing practises in the world. Four books were selected for this research. Several old customs and practices such as drawing kolam, seclusion of females during menstruation, using cow dung for cleaning floors, wearing thread with Thaayathu, wearing silk clothes, worshipingpeepal tree,sleeping in specific directions etc…are some of the old customs, practices and superstitious beliefs having beneficial effects on human health. In the name of rationality, people consider them as mere superstitious beliefsand fail to follow. This paper will throw light on the socalled superstitious beliefs, old customs and practices followed especially in South India, which have real beneficial effects on human health.
Keywords: superstitious beliefs; South India